A Land of Canaan : His Love Endures Forever - Book 3 - Wiseman, Beth 1962- (Nashville, Tenn. : Thomas Nelson, 2012)
When Danielle Kent becomes pregnant with Aaron Lapp's child, her Amish friend Levi Detweiler is sure that Aaron, an Old Order Amish, will do the right thing and marry Danielle, but when that doesn't happen, God calls on Levi to marry her.
Keywords: Amish -- Fiction; Colorado -- Fiction; Christian fiction; Love stories